Pengaruh Komunikasi, Dukungan Organisasi, dan Lingkungan Kerja Fisik Terhadap Kepuasan Kerja Karyawan di PT. Aryana Sinar Abadi - Deviko Andi Putra; Udik Jatmika; Nur Hidayati (Digital Bisnis: Jurnal Publikasi Ilmu Manajemen dan E-Commerce, 2024)
Lack of communication problems between employees and superiors causes conflict at work, besides that there is an error in communication between each section or department, seen from the results of work that are not as expected by superiors or other departments because there is no clear direction given to employees the. Through communication too, someone can convey everything related to his work. The existence of good communication between employees and company leaders is very important to be able to see the level of satisfaction. The purpose of this research is to find out and explain the influence partially and simultaneously between employees and superiors to increase job satisfaction. This type of research approach is quantitative, with a population of 30 employees using saturated sampling as a sample determination model. Data analysis techniques were carried out using descriptive analysis and inferential statistics through validity, reliability, classical assumption tests, multiple linear regression tests, t tests and F tests. The results of this research showed that 1) partially the communication variable partially has a positive and significant effect on employee job satisfaction. 2) The organizational support variable partially has a positive and significant effect on employee job satisfaction. 3) The physical work environment variable has a positive and significant effect on employee job satisfaction. 4) Simultaneously the variables of communication, organizational support, and the physical work environment jointly influence the variable of job satisfaction.